GRAIN SIZE AND MORPHOMETRICAL CHARACTERISTICS OF BOEOTIAN KIFISOS STREAM GRAVEL-BED AND THEIR GEOLOGICAL IMPORTANCE - Καρκάνας Α. Π.; Κοντόπουλος Ν. Σ. (Bulletin of the Geological Society of Greece, 2018)
This work studies the lithology, mean size, roundness, sphericity and form of gravels of Boeotian Kifisos river bed, in eleven stations of sampling in middlestream area. The lithology of gravels are limestone, sandstone, chert and igneous. Limestone percentage averages 78.89%, sandstone 11.40%, chert 6.48% and igneous 7.23%. The changes in litho logy with distance of transport is due mostly to influx of new material and partly to abration and breakage of less resistant lithologies (limestone, igneous, sandstone). The mean size of the gravels of all lithologies decreases with the distance of transport. This is due to mainly in the selective sorting because of the reduction of the river slope. The roundness according to Powers (1982) for limestone, sandstone, chert and igneous gravels is 3,81, 4,65, 2,13 and 3,01 respectively. The sphericity of the limestone, sandstone, chert and igneous gravels is 0,70, 0,66, 0,72 and 0,70 respectively. The arithmetic mean of sphericity of total of gravels is 0,69. The roundness is not related with the distance of transport. This suggests that this parameter has acquired the biggest values of degree of roundness before the first station of sampling. Also, the sphericity of the non-resistance lithologies (limestone, sandstone, igneous) does not show any relationship with distance. This suggests a breakage along the bedding in combination with anisotropic wear. On the contrary the sphericity of chert decreases with distance because it were chipped during transport. Boeotian Kifisos river has the tendency to produce more spherical and discoidal gravels than blade and prolate. Moreover the two first forms tend to decrease with the distance of transport while this does not happen with the remainder two forms.